Outcomes of a Proximal Workplace Intervention Against Workplace Bullying and Harassment: A Protocol for a Cluster Randomized Controlled Trial Among Norwegian Industrial Workers - Einarsen, Kari; Nielsen, Morten Birkeland; Hetland, Jørn; Olsen, Olav Kjellevold; Zahlquist, Lena; Mikkelsen, Eva Gemzøe; Koløen, Justine; Einarsen, Ståle Valvatne (Frontiers in Psychology, 2020)
Background: Workplace bullying is an important and prevalent risk factors for health impairment, reduced workability and lowered efficiency among both targets and observers. Development and tests of effective organizational intervention strategies is therefore highly important. The present study describes the background, design and protocol of a cluster randomized controlled trial evaluating the effectiveness of an organization-wide intervention on preventing workplace bullying with a focus on promoting active and constructive bystander interventionbehavior. The main overarching goal is to develop an easy to use and standardized organizational intervention based on theory and research in the role of bystanders in bullying situations with the potential of reducing the prevalence of workplace bullying. Methods/design: Using a full RCT design, this project will empirically test the outcomes of an intervention program targeting bullying and harassment as the main distal outcomes and perceived behavioral control and helping behavior among bystanders as the main proximal outcome. A one-year cluster randomized controlled design will be utilized, in which controls will also receive the intervention. About 1500 workers from two different locations of a Norwegian industrial company will be randomized into one intervention group and two control groups with at least 400 workers in each group. A survey will be conducted electronically. With a total of three assessments over 10-12 months, the time interval between the measurement times will be four months. Thus, the data collection will take place at baseline, completion of the intervention and at four months follow-up. Discussion: This study primarily aims to develop, implement and evaluate an intervention based on the abovementioned features with the ultimate aim of reducing the prevalence of workplace bullying, by awareness raising and training of bystanders. Manager involvement and involvement of the union representative and the elected health and safety representatives is an important feature of the program. Results of the intervention study will provide important information regarding the effectiveness of preventive interventions against workplace bulling when focusing on bystanders, and particularly so regarding the role of bystander awareness, bystander self-efficacy, bystander behavioral control on the one hand and the prevalence of bullying and harassment on the other.